Comparison between Effects of Intralesional Platelet Rich Plasma and Corticosteroid Injection on Pain and Functional Outcome in Patients with Lateral Epicondylitis of Elbow (Journal of Monno Medical College, 2024)
Background: A debilitating and painful elbow problem is lateral epicondylitis.Objective: In this study, pain and functional outcomes were examined in relation to intralesional platelet-rich plasma (PRP) and corticosteroid injections patients with lateral epicondylitis.Methodology: This randomized experimental study was done in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2017 to February 2018. Thirty patients with diagnosed lateral epicondylitis, aged between 21- 60 years and had been ill for more than a month were enrolled and randomly assigned into two groups. In Group A received two doses of intralesional PRP injection, and Group B received two doses of intralesional corticosteroid injection. Pain and functional outcomes were evaluated by using a visual analog scale (VAS) for pain and a patient-rated tennis elbow assessment (PRTEE) questionnaire, respectively. In the lateral epicondylar region, intralesional PRP or corticosteroids were administered during the first (week 1=W1) and fourth (week 7=W7) treatment visits.Results: The findings revealed a statistically significant decline in pain over time, as well as improvements of functional outcomes in both groups as evidenced by significantly lower VAS scores and lower PRTEE scores up to 11 weeks post-injection. There was no discernible difference in progress between the two groups up until W1 to W9 scores, however at the eleventh week, group A showed greater improvement than group B (p